ANALISIS DETERMINAN DAN SKALA EFISIENSI PRODUKSI INDUSTRI KERAJINAN KAYU DI PROVINSI BALI TAHUN 2017-2022 - Nandari Dewi, Ida Ayu Bintang; Meydianawathi, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025DO - 10.24843/EEB.2025.v14.i05.p05, 2025)
The wood craft industry plays an important role in Bali's economy outside of the tourism sector, particularly through its contribution to job creation and increased regional exports. By applying Cobb-Douglas function analysis, this study aims to examine the various factors that influence the production and scale efficiency of the wood craft industry in Bali Province in 2017-2022. The results of the analysis using the fixed effect model panel data regression method show that the number of business units, labor, and Covid-19 dummy have no significant effect on production, while investment has a significant negative effect. These results are influenced by various factors such as low labor productivity, market fragmentation, and untargeted investment allocation. Meanwhile, the raw material variable has a significant positive effect on the production of the wood craft industry in Bali Province in 2017-2022. The efficiency scale of this industry is in the Decreasing Return to Scale (DRTS) condition, meaning that an increase in input does not result in a comparable increase in output. Therefore, strategies are needed to improve production efficiency, more optimal investment management, and more effective utilization of raw materials. In addition, innovation in production techniques and improving labor skills are important aspects in improving the competitiveness of the wood craft industry in Bali Province.